A plug-and-play ripple mitigation approach for DC-links in hybrid systems - Li,S; Lee,ATL; Siew-Chong-Tan; Hui,SY (IEEE, 2016)
In this paper, a plug-and-play ripple mitigation technique is proposed. It requires only the sensing of the DC-link voltage and can operate fully independently to remove the low-frequency voltage ripple. The proposed technique is nonintrusive to the existing hardware and enables hot-swap operation without disrupting the normal functionality of the existing power system. It is user-friendly, modular and suitable for plug-and-play operation. The experimental results demonstrate the effectiveness of the ripple-mitigation capability of the proposed device. The DC-link voltage ripple in a 110 W miniature hybrid system comprising an AC/DC converter and two resistive loads is shown to be significantly reduced from 61 V to only 3.3 V. Moreover, it is shown that with the proposed device, the system reliability has been improved by alleviating the components' thermal stresses.